2010
DOI: 10.1007/s00540-010-1013-3
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine spray 10 min prior to intubation: effects on postoperative sore throat

Abstract: A sore throat is the most frequent adverse side effect of general anesthesia. The purpose of this study was to compare the different types and timing of lidocaine application based on the effectiveness of reducing postoperative sore throat (POST) after endotracheal intubation. In group A, 8% lidocaine was sprayed on laryngopharyngeal structures immediately before intubation, and the distal ends of the endotracheal tubes (ETTs) were lubricated with 2% lidocaine gel. In group B, 8% lidocaine was sprayed, and ETT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…In two published studies to date, the authors found that patients in the age group 30–40 years (women and men) were at an increased risk of POST . In other studies, older patients > 60 years (women) or ≤ 70 years (women and men) have been suggested to be at an increased risk. In our study, women > 40 years were more prone to develop POST, but not the men.…”
Section: Discussionmentioning
confidence: 96%
“…In two published studies to date, the authors found that patients in the age group 30–40 years (women and men) were at an increased risk of POST . In other studies, older patients > 60 years (women) or ≤ 70 years (women and men) have been suggested to be at an increased risk. In our study, women > 40 years were more prone to develop POST, but not the men.…”
Section: Discussionmentioning
confidence: 96%
“…It has been shown that chemical additives in some endotracheal tube lubricants, including local anesthetics, can irritate airway mucosa, potentially causing airway mucosal damage and ultimately leading to an increased incidence and severity of POST. 3 The article did not clearly explain whether the 0.1% triamcinolone acetonide paste was a special preparation for airway mucosal use, hence, we suggest cautious interpretation of these findings.…”
mentioning
confidence: 84%
“…We thank Fu Shan Xue and colleagues for their interest in our recent article [1]. First, there were no exclusion criteria in our study after the obtaining of informed consent.…”
Section: In Replymentioning
confidence: 99%